Valuation and Appreciation of Biodiversity: The “Maintenance of Options” Provided by the Variety of Life - Faith, Daniel P. (Frontiers in Ecology and Evolution, 2021)
“Nature’s contributions to people” (NCP) is an important expansion beyond the standard ecosystem services framework, particularly as a pathway to better address global/regional biodiversity values. NCP 18, “maintenance of options”, refers broadly to the capacity of ecosystems, habitats, species or genotypes to keep options open to support a good quality of life. “Biodiversity”, interpreted as living variation, is an important, but under-appreciated, aspect of “maintenance of options”. IPBES refers to “the ‘option values of biodiversity’, that is, the value of maintaining living variation in order to provide possible future uses and benefits.” IPBES assessments include biodiversity option value, and use phylogenetic diversity as an indicator of change in status of NCP18. IPBES also notes the need for greater appreciation of maintenance of options. Popular ecosystem services framings forget the long history of consideration of these benefits of biotic diversity to humanity, and their normative links. Popular ecological definitions mean that many current valuations of “biodiversity” neglect the benefits of biodiversity-as-variety. Economic valuations of “biodiversity” typically have focussed on ecosystem aspects, not variety; related ecosystems framings value “biodiversity” with a focus on those critical elements relating to functioning of ecosystems. Greater appreciation of biodiversity option value and NCP18 may depend on clear messaging from academia, Integrating multiple values including the value of variety itself, highlighting the link between biodiversity and intergenerational justice, and communicating stories of past surprising discoveries of benefits from species to highlight biodiversity as an ongoing source of future benefits.